Melanoma Immunotherapy: Next-Generation Biomarkers - Hogan, Sabrina A.; Levesque, Mitchell P.; Cheng, Phil F. (Frontiers in Oncology, 2018)
The recent emergence of cancer immunotherapies initiated a significant shift in the clinical management of metastatic melanoma. Prior to 2011, melanoma patients only had palliative treatment solutions which offered little to no survival benefit. In 2018, with immunotherapy, melanoma patients can now contemplate durable or even complete remission. Treatment with novel immune checkpoint inhibitors (ICIs), anti-CTLA-4 and anti-PD-1, clearly result in superior median and long-term survivals compared to standard chemotherapy, however, more than half of the patients do not respond to immune checkpoint blockade. Currently, clinicians do not have any effective way to stratify melanoma patients for immunotherapies. Research is now focusing on identifying biomarkers which could predict a patient’s response prior treatment initiation (or very early during treatment course), in order to maximize therapeutic efficacy, avoid unnecessary costs, and undesirable heavy side effects for the patient. Given the rapid developments in this field and the translational potential for some of the biomarkers, we will summarize the current state of biomarker research for immunotherapy in melanoma, with an emphasis on omics technologies like next generation sequencing (NGS) and mass cytometry (CyTOF).